Amphibia, Anura, Bufonidae, Melanophryniscus krauczuki: geographic distribution map and first record for Paraguay - Brusquetti Estrada, Francisco Adolfo (2007)
Amphibia, Anura, Bufonidae, Melanophryniscus krauczuki: Geographic distribution map and first record for Paraguay.